Decoding plant thermosensors: mechanism of temperature perception and stress adaption - Zhu, Tongdan; Cheng, Xi; Li, Chengwen; Li, Ye; Pan, Changtian; Lu, Gang (Frontiers in Plant Science, 2025)
Global climate change, characterized by increased frequency and intensity of extreme temperature events, poses significant challenges to plant survival and crop productivity. While considerable research has elucidated plant responses to temperature stress, the molecular mechanisms, particularly those involved in temperature sensing, remain incompletely understood. Thermosensors in plants play a crucial role in translating temperature signals into cellular responses, initiating the downstream signaling cascades that govern adaptive processes. This review highlights recent advances in the identification and classification of plant thermosensors, exploring their physiological roles and the biochemical mechanisms by which they sense temperature changes. We also address the challenges in thermosensor discovery and discuss emerging strategies to uncover novel thermosensory mechanisms, with implications for improving plant resilience to temperature stress in the face of a rapidly changing climate.